Penerapan Metode Iteratif Lanczos–Hybrid Regularization Pada Restorasi Citra Digital Hasil Scan - Sumarni Sumarni (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Digital image management generally refers to processing two-dimensional images using a computer in a broader context. Image restoration is image pemamangan by eliminating or reducing degradation of the image that occurs due to the process of image acquisition. The scanned image is the process of moving images (images) using a scanner which often experiences a decrease in image quality (degraded). This results in inaccurate results in digital image processing such as blur / blur, spots, dual images, over saturated colors, and pixel errors. Caused by external factors (noise). Iterative lanczos-Hybrid Reqularization method is one of the choices of effective methods in solving the blur or noise problem that causes the image quality to decrease or not match the original image. In the process of digital image restoration scan results that have degraded can be maximized well from the original image, in this study the Iterative lanczos-Hybrid Reqularization method of image restoration used can provide more optimal results with more effective and efficient time.